Signal processing analysis of arrhythmias detection - Koh, Ruben Wai Hong. (2013)
Heart problems in patients are often classified as Arrhythmias. The term “Arrhythmia” means any deviation of the heart electrical impulses from its regular sequence. Such deviation in the impulses may occur too rapidly, too sluggish, or too erratically, causing the heart to respond in a similarly corresponding manner. When the heart fails to response normally, blood does not flow to the rest of our body normally too. This causes the organs in the body like the lungs and brains to shut down. In serious cases, Arrhythmias can be fatal.